2016
DOI: 10.1016/j.arth.2016.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Which Hospital and Clinical Factors Drive 30- and 90-Day Readmission After TKA?

Abstract: The results of this study support further optimization of anti-infection measures, both intraoperative and postoperative, to reduce the broad variation in hospital readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 13 publications
5
68
5
Order By: Relevance
“…These include surgeon volume, operative time, general anesthesia, use of anticoagulation other than aspirin, increased length of hospital stay, and discharge to an inpatient rehabilitation facility [43][44][45][46][47]. Kurtz et al [44] found that increased surgeon volume has a protective effect against readmissions after TJA. Each additional surgeon volume of 100 procedures leads to 6% less risk of readmission.…”
Section: Perioperative Risks For Readmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include surgeon volume, operative time, general anesthesia, use of anticoagulation other than aspirin, increased length of hospital stay, and discharge to an inpatient rehabilitation facility [43][44][45][46][47]. Kurtz et al [44] found that increased surgeon volume has a protective effect against readmissions after TJA. Each additional surgeon volume of 100 procedures leads to 6% less risk of readmission.…”
Section: Perioperative Risks For Readmissionmentioning
confidence: 99%
“…This may be partially due to the fact that increased hospital length of stay can increase the risk of hospital-acquired infections and thromboembolic events. Lastly, multiple studies have shown that discharge to inpatient facilities is associated with worse outcomes and increased rates of readmission [43][44][45][46][47]. A study by Fu et al [47] showed that discharge to inpatient facilities is independently associated with a higher rate of readmission and increased risk for a number of postdischarge complications.…”
Section: Perioperative Risks For Readmissionmentioning
confidence: 99%
“…15 A recent study by Kurtz et al reported that Medicare beneficiaries discharged home had 25% less risk for 30-day all-cause hospital readmission than those discharged to inpatient post-acute settings. 17 Nonetheless, these studies only provide partial information regarding the most prevalent discharge settings following TKA and their impact on hospital readmission, particularly 30-day unplanned readmission in Medicare beneficiaries, which is the primary quality indicator of the readmission reduction program. 1 …”
Section: Discussionmentioning
confidence: 99%
“…1417 Commonly cited reasons for hospital readmission at 30 or 90 days include problems associated with the joint replacement procedure itself (infection or joint stiffness) 16, 1821 or respiratory or cardiovascular events. 9, 20 Other reported clinical factors increasing 30- or 90-day readmission include longer hospital length of stay, general anesthesia, blood transfusions, increased comorbidity, rheumatoid arthritis, venous thromboembolism and urinary tract infections.…”
mentioning
confidence: 99%
See 1 more Smart Citation